KETERKAITAN “TAKUT AKAN TUHAN” DAN “MEMBENCI KEJAHATAN” TERHADAP PEMBENTUKAN KARAKTER: KAJIAN HERMENEUTIK BERDASARKAN AMSAL 8:13 - Pattinaja, Aska Aprilano (STT Ekklesia Pontianak, 2024)
Abstract: The purpose of this study is to examine the interrelationship between 'fear of God' and 'hatred of evil' as they relate to individual character development. This research focuses on answering two questions, firstly, is the meaning of fearing God the same as hating evil, and secondly, can hating evil be a guarantee of commitment to fearing God? There is a gap in research that explores character formation based on the nature of the fear of the Lord in Proverbs 8:13 as an answer to the questions posed. Therefore, based on the qualitative research method and the hermeneutic approach of the sub-genre of wisdom literature, this study was carried out to argue that: first, hating evil is a manifestation of the choice to fear God; second, there are three serious commitments in hating evil that have implications for character building, namely 1). Not to be arrogant and haughty; 2) Not to commit evil deeds; and 3) Not to speak misleading words. The results of this study show that the fear of God is an important foundation for character development. Abstrak: Tujuan dari penelitian ini adalah mengkaji keterkaitan dari